MEREPRESENTASIKAN SENI PERTUNJUKAN TRADISI MELALUI PENDEKATAN ETNODOKUMENTER - Gerzon R. Ayawaila (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
To perform the representation of an art tradition is not simple. We need approachment method because the rites have sense of spirit and myth. This is the same as we record the sense of life from local genuine people with the way of life in their culture system. Therefore we must be very careful when we recorded and represented the whole spirit of local tradition culture of their social life. This note was trying to analyze how we could represent the performing of an art tradition through film or video, from two point of views, in two different disciplines: Visual Anthropology and Documentary Film. Camera or audiovisual is a research tool for Anthropology. Sinematography is a process of an abstract observation but it is quite different from the fieldworker’s inscribe notebook where the information is preserved in literate code. Sinematography could gather selected and specific information, recorded the realism of time and motion or the psychological reality from varieties of interpersonal relations. With the camera we can analyze the way of action of an art tradition was performed, where so many elements are in motion together. In this situation human memory and notebook records become wholly inadequate. This note was written with the purpose of not to some normative answer about where the ideal point of view between anthropology and documentary approachment method. Between two distinguished approachment point of view, maybe we could have another creative approachment in same reason with comparative perspective, to records and to represent the performing of an art tradition in their own reality.Key word: documentary, tradition art performing, visual language